A Novel Ferrocene‐Based Calix[4]arene as an Efficient Optical and Electrochemical Sensor for Highly Selective Fluoride Recognition. Issue 13 (4th April 2019) - Hosseinzadeh, Rahman; Maliji, Farzaneh; Golchoubian, Hamid; Bekhradnia, Ahmadreza
Abstract: A new tetra ferrocene‐triazole‐amide functionalized calix[4]arene as an effective optical and electrochemical anion sensor was successfully synthesized in high yield. The structure of the resulted compound ( 5, 11, 17, 23‐tetra(ferrocenyl‐1H‐triazolo‐acetamido)‐25, 26, 27, 28‐ tetrabutyloxycalix[4]arene, 6 ) was characterized with NMR spectra and elemental analysis. The anion binding properties of the compound in the presence of different anions were studied by various techniques (UV‐Vis, fluorescence, cyclic voltammetry (CV) and 1 H NMR titration), which showed high selectivity and remarkable sensitivity toward fluoride ion (F − ). The association constant (Ka ) and the limit of detection (LOD) were determined to be 5.35×10 +8 M −2 and 2.98×10 −6 M, respectively. The results indicate this compound could act as an efficient sensor for fluoride anion in the presence of other common anions. Abstract : A novel ferrocene‐based receptor as an effective optical and electrochemical anion sensor was synthesized. The structure of compound was fully characterized. The anion binding properties of the compound in the presence of different anions showed high selectivity and remarkable sensitivity toward fluoride ion (F − ). The association constant (Ka ) and the limit of detection (LOD) were determined. In this receptor, ferrocene, amide and triazole moieties efficiently contribute to anion binding and detection.